Optimization and application of a mouse challenge model for Mumps virus - Yajing Zhang; Benjie Chai; Fei Huang; Biao Niu; Yangyang Liu; Pengpeng Zhou; Hui Wang; Yue Guo; Zhenfang Fu; Qi An; Dayong Tian (Vaccine: X)
Abstract:: Mumps is an acute respiratory infectious disease that occasionally experiences outbreaks even in countries with high vaccination rates. This indicates potential antigenic differences between currently available vaccine strains and circulating wild-type viruses. Therefore, it is crucial to evaluate the vaccine's protective efficacy against the epidemic strain. In this study, we injected IFN-α/βR−/− mice with genotype F or G wild-type strains via the tail vein. The mumps virus rapidly replicated and maintained high levels in the blood. Furthermore, prior immunization of IFN-α/βR−/− mice with vaccine strain significantly inhibited viral replication in vivo. Consequently, we have optimized a valuable model for assessing the effectiveness of MuV vaccines.